Species diversity and endemism of five major Malesian islands: diversity–area relationships - Marco C. Roos; Paul J. A. Keßler; S. Robbert Gradstein; Pieter Baas (Journal of Biogeography, 2004)
Aim A comparison of biodiversity patterns within Malesia in relation to surface area. Location Analysis of the patterns in species richness and endemism of vascular plants in the five major Malesian islands, i.e. Java, Sulawesi, Sumatra, Borneo and New Guinea. Methods Available data on species richness and species ranges in correlation with the surface area of the respective islands were examined in this work. Estimations of total species numbers for these islands are presented based on extrapolation of all available published Flora Malesiana information and recent checklists, all in all comprising 12,000 different species. The regression analysis of overall species richness and endemism were studied for all species together as well as for different plant families to compare the fit with the Arrhenius species–area model. Results The five islands form a series of independent areas of increasing size suited for an analysis of the species–area relationships at the regional scale. All species taken together and those of families with even distribution throughout Malesia show significant species–area relationships. Non‐significant relationships were detected in families with western or eastern‐centred Malesian distribution patterns. Relationships between number of endemic species and surface area are significant for all species and for the majority of the families with significant species–area relationships. Main conclusions Species–area relationships of families appear to be dependent on species number. Families with high numbers of species usually have a significant species–area relationship whereas small families have not. For the families that display an eastern or western Malesian centred pattern, a historical biogeographical explanation should be invoked. Island surface area appears to be a predictor for island percent endemism in Malesian vascular plants. None of the islands appears to be a hotspot of endemism nor of species diversity, as no significant departure from the Arrhenius model was noted for any of them.